BANK LENDING TO SMALL BUSINESSES - o’g’li, Karimjonov Doniyorbek Ibrohimjon (Antis Publisher, 2024)
The position on the advisability of using borrowed financial resources at all stages of small business development is substantiated, the problems of bank lending to small businesses are analyzed and directions for its expansion and improvement are proposed